Investigating the association between physical fitness and blood pressure among healthcare workers in Indonesia - Wahyu Sulistiadi; Riswandy Wasir; Astriana; Badra Al Aufa; Sri Rahayu; Wasir Thalib; Fadilah Aulia Rahma (Springer, 2024)
Abstract Background Non-communicable diseases (NCDs), including hypertension and cardiovascular diseases, are significant health concerns in Indonesia. Healthcare workers are particularly vulnerable due to occupational stress and physical inactivity. This study aimed to investigate the relationship between physical fitness and blood pressure among healthcare workers, particularly nurses in Indonesia. Methods A cross-sectional study was conducted from July to August 2023 at a hospital in Lampung Province. A total of 92 nurses volunteered to participate. Physical fitness was assessed using the Rockport Walking Test (RWT), and blood pressure was measured before and three minutes after the RWT. Body mass index (BMI) and demographic data were also collected. Paired t-tests were used to analyze changes in blood pressure. Results Before the RWT, 78.3% of participants had normal blood pressure, increasing to 90.2% post-RWT. The mean decrease in blood pressure was 1.93 mmHg (p = 0.031). Despite 63.0% of participants having poor physical fitness, moderate physical activity, as measured by the RWT, was associated with improved cardiovascular outcomes. Conclusion This study found an association between physical fitness and blood pressure among healthcare workers, particularly nurses. While the cross-sectional design limits causal conclusions, the findings suggest that promoting physical activity could help manage blood pressure and reduce NCD risks in this critical workforce.